An ecological study of the ixodid tick rhipicephalus glabroscutatum (Du Toit, 1941) - Macivor, Keith Malcolm de Falloux (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1983)
An intensive study was conducted on the free-living larvae and parasitic life stages of R.glabroscutatum on Angora and Boer goats in the Uitenhage district. Free-living larvae exhibited periods of maximum relative abundance during months of generally lower rainfall, from the end of autumn to the beginning of spring. Relative larval abundance in open and gully sites was low while larvae were rarely found in bush sites. Relative abundance was higher at 20h00 than at 08h00 and 14h00. Repeated sampling in the same areas did not reduce larval numbers. Over 99% of parasitic ticks removed from Angora and Boer goats were located on the feet. The annual occurrence of a low and variable number of parasitic immatures was synchronous with the occurrence of free-living larvae. High, less variable numbers of adult ticks were removed from goat feet from September to December, the highest numbers being recorded during October and November. The occurrence of a single period of parasitic adult abundance annually indicated a life cycle with 1 generation per anum. There were higher numbers of adult ticks on the feet of the Angora goats than on the Boer goats. Adult numbers were higher on the hind feet of both breeds of goats than on the front feet. R.glabroscutatum adults seem to be implicated in the aetiology of foot abscesses since more infections were observed in Angora goats than in Boer goats and on the hind feet rather than the front feet within both goat groups. In addition R.glabroscutatum adults attached at interdigital sites where abscesses also originated and reached highest numbers in October and November when abscesses were most frequently observed. A review of distribution and host records indicated that R.glabroscutatum was limited in its distribution to the eastern Cape Province, being primarily located in South Africa's major mohair producing areas. R.glabroscutatum was classed an obligative xerophile on the basis of its recorded occurrence in non coastal areas with a low annual rainfall and Karoo and Karroid Bush vegetation. Host records for R.glabroscutatum included 10 species of wild ungulate, sheep, goats and cattle. The common site of occurrence on small stock and on small to medium sized wild animals appeared to be the legs and feet.
Keywords: Ticks -- Control -- South Africa -- Eastern; Cape Parasites -- South Africa -- Eastern Cape; Rhipicephalus -- South Africa -- Eastern Cape; Angora goat -- South Africa -- Eastern Cape; Larvae -- South Africa -- Eastern Cape